Pengaruh Corporate Governance Dan Karakteristik Perusahaan Terhadap Tax Avoidance Di Bursa Efek Indonesia - Putri, Ida Zulaikha Wahyu (2016)
The purpose of this study was to test the effect on the institutional ownership tax avoidance. To test the effect on the audit committee of tax avoidance. To test the effect on the quality of audits tax avoidance. To test the proportion of independent board effect on tax avoidance. To test the effect on the company size of tax avoidance. To test the effect on the company's risk of tax avoidance. The samples are manufacturing companies listed in Indonesia Stock Exchange and had complete data on institutional ownership, the audit committee, audit quality, the proportion of independent board, the size of the company, and the company's risk consistently over the period 2011-2013. The samples used by 23 companies manufacturing for 3 years in a row - a row. This research uses descriptive statistical analysis, such as the classical assumption of normality test, multicollinearity test, autocorrelation test, heteroscedasticity test and test hypotheses in the form of test multiple linear regression analysis, a statistical test t, F statistical test, test the coefficient of determination (R ²). Results from this study showed that the variables that affect tax avoidance in manufacturing companies is the risk of the company as evidenced by the significant value <0.05 while variable that does not affect the tax avoidance in manufacturing companies are institutional ownership, the audit committee, audit quality, the proportion of independent board, and the size of the company as evidenced by the significant value> 0.05.